Compressional Physics of Binary Mixture of Dried Andrographis paniculata and Moringa oleifera Leaves - Isaac, Johnson Ajeh; Ekere, Kokonne Elizabeth; Ezekiel, Ekeh; Galadima, Isa Hayatu; Abdulahi, Rashida; Samali, Ayuba (Borneo Journal of Pharmacy, 2021)
Traditionally, the leafy part of Andrographis paniculata and Moringa oleifera have been widely reported to manage hypertension. Investigation of its pharmacological actions justifies its use. As part of formulation studies to standardize them, this study focused on their compaction and compression properties. Compacts equivalent to 250 mg of A. paniculata and M. oleifera were produced by compressing powders and granules at various compression pressure. Results show that M. oleifera met the WHO limit for ash values. Relative density values for granulated batches were higher, while their moisture content values were lower when compared to those of direct compression. The result from Heckel plots shows that batches deform mainly by plastic flow. For Kawakita plots, values of 1/b show that batches containing microcrystalline cellulose were less cohesive. The plot of tensile strength signifies that granulated batches achieved maximum crushing strength faster at low pressure. Formulations containing maize starch were shown to have higher percent porosity, and granulated batches gave higher values for apparent density-pressure relationship and lower friability values. Tablets produced by the wet granulation method showed better compression and compaction properties than those formulated by direct compression.